Integrated advertising, promotion, and marketing communications - Clow, Kenneth E. (Pearson, 2018)
ntegrated Advertising, Promotion, and Marketing Communications speaks to an evolved definition of integrated marketing and teaches students how to effectively communicate in the business world. It champions the importance of integrating all marketing communications and helps students understand how communications are produced and transmitted. This text covers advertising and promotions, the role of social media, blogs, mobile messaging, and other marketing tactics. To help students retain ideas, each chapter includes tools that allow students to apply concepts to real-life situations.